"Raças humanas" como uma questão sociocientífica: implicações para a formação de professores de ciências - Carvalho, Thabata Rodrigues de (2019)
In this investigation, we sought to comprehend the implications of the discussions about “Human Races” and its socio-scientific aspects on the training of Science teachers.Through the Critic Theory by Jürgen Habermas, we based our research on a communicative perspecti-ve of education. In the context of a teachers training course, we developed this work and we made our data based on theoretical-methodological references of the action research. Those data were registered through personal observations and recordings of the developed activities. In our analysis, wesought to evidence the pragmatic and propositional contents of the speeches. Thus, wesought to comprehend both the sense of speeches and the intentionality of the speaker. Our data allowed us to emphazise the formative potential of the subject “Human Races” and its socio-scientific aspects discussed in a communicative teaching perspective. Wehigh light the work in interdisciplinary group sand the collective reflections as potential means to the development of teacher autonomy and to the deconstruction of positivist and fragmented conception of the scientific knowledge of the teachers in training. The approach of the SSI "Human Races" enabled teachers in training to have spaces of communicative interaction, from which they could rethink questions about Science teaching, by considering their ethical and value dimensions.Therefore, we consider that this approach can contribute to science education based on principles of democracy and social justice.